2021
DOI: 10.1021/acsami.1c10559
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Loading with Polypyrrole Nanoparticles for Trace-Level Detection of Ammonia at Room Temperature

Abstract: The outstanding versatility of graphene for surface functionalization has been exploited by its decoration with synthesized polypyrrole (PPy) nanoparticles (NPs). A green, facile, and easily scalable for mass production nanocomposite development was proposed, and the resulting PPy@Graphene was implemented in chemoresistive gas sensors able to detect trace levels of ammonia (NH 3 ) under room-temperature conditions. Gas exposure for 5 min revealed that the presence of nanoparticles decora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…According to the literature, we know that PPy is very sensitive toward aminebased compounds 40,52 and NH 3. 53,54 As results show, the Au-IDEs/S-PPyMPs, as well as Au-IDEs/S-PPyMPs/AgNPs, respond to MA, DMA, TMA, EA, and TEA. Clearly, the response of Au-IDEs/S-PPyMPs/AgNPs to NH 3 is better than that of tested amine-based compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the literature, we know that PPy is very sensitive toward aminebased compounds 40,52 and NH 3. 53,54 As results show, the Au-IDEs/S-PPyMPs, as well as Au-IDEs/S-PPyMPs/AgNPs, respond to MA, DMA, TMA, EA, and TEA. Clearly, the response of Au-IDEs/S-PPyMPs/AgNPs to NH 3 is better than that of tested amine-based compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Figure B indicates the dynamic response behavior of the Au-IDEs/S-PPyMPs toward NH 3 vapor. Previous works have revealed that the PPy is a p-type semiconductor with high hole mobility, showing excellent sensitivity toward amine-based compounds. ,, When the PPy surface is exposed to an amine, the amine molecules will attack the polymer backbone, decreasing the holes, which consequently results in an increase in the electrical resistance. The response of Au-IDEs/S-PPyMPs to the various concentrations of NH 3 returns to its initial resistance after exposure to air.…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s spectrum of γ-FeOOH can be attributed to adventitious carbon species . In Figure a, the peak fitting analysis of C 1s for PFL/CDs-2 is deconvoluted into five components with the most predominant peak at 283.5 eV corresponding to the C sp 3 configuration (C α ) in the surface functional groups of pyrrole ring and C-dots. , In contrast, the component located at 283 eV corresponds to photoelectrons emitted from the C sp 2 configuration (C β ) of aromatic C=C bonds . The peaks corresponding to 285 eV are attributed to C–O/C–N bonds present in the pyrrole ring and C-dots surface.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a shows the graphene surface once it was deposited. A highly porous surface can be noticed (BET area of 730 m 2 /g according to previous results), which can be interesting from the sensing point of view. Moreover, Figure b confirms the well-dispersed crystalline cluster particles supported on graphene.…”
Section: Resultsmentioning
confidence: 99%